COMPARATIVE ANALYSIS OF JOINT STOCK COMPANIES OF KAZAKHSTAN AND FOREIGN COUNTRIES (Journal of actual problems of jurisprudence, 2020)
The market transformation of Kazakhstan’s economy has caused a revival of Kazakhstan’s shareholdinglaw. Among the most important players in the market economy of any country that has alreadyreached the required level of capital-building are economic partnerships and societies.In today’s market transformation, the company as an organizational form of business takes on specialimportance. The classic function of the company is to attract and long-term accumulation of capital. Theavailability of capital is vital for businesses. The shareholder form is optimal for anonymously combininga large number of participants, allows to attract additional investments by issuing shares, “removes” thedifferences between different forms of capital and thus facilitates their overflow ingessing out industryin the industry. Economic growth needs investment. One of the most effective ways to concentrate freeresources and turn them into investments are joint-stock companies.Method of research. The methodological basis of scientific research is a set of methods of scientificknowledge, among which the leading place is occupied by the dialectical method. This scientific articleuses General scientific methods of cognition, which, first of all, should include formal logical methods(analysis, synthesis, induction, deduction, analogy), as well as special legal methods (formal legal, themethod of comparative law and system analysis).The theoretical basis of the study was the theoretical and scientific-practical work of Russian scientistson the legal regulation of share capital, changes in the structure of shareholders in the reorganizationof joint-stock companies, including the change of ownership of a joint-stock company, as well asfundamental work in the theory of civil and corporate legislation.Key words: joint-stock company, legal entity, entrepreneur, authorized capital, legal status, procedureof creation, activity, rights and obligations of shareholders, procedure of formation and functioningof bodies of joint-stock company.